Solvent-controlled and solvent-dependent strategies for the synthesis of multicolor carbon dots for pH sensing and cell imaging. Issue 31 (25th July 2019) - Bai, Jianliang; Ma, Yusha; Yuan, Guojun; Chen, Xu; Mei, Jing; Zhang, Lu; Ren, Lili
Abstract : Solvent-controlled, pH-dependent and solvent-dependent strategies are proposed to obtain multicolor carbon dots using the same precursor. Abstract : Carbon dots (CDs), especially multicolor carbon dots, have tremendous potential applications in light-emitting diodes, photocatalysis, bioimaging and sensing; however, the production of carbon dots with multicolor emissions involving tunable PL (photo-luminescence) from blue to red is still difficult. Here, we proposed solvent-controlled and solvent-dependent strategies to obtain multicolor carbon dots via adjusting the graphitization degree and surface functional groups. Blue and red carbon dots were successfully prepared by the hydrothermal method using p -phenylenediamine and oxalic acid. By simply varying the solvent in the reaction, the fluorescence emissions of CDs notably shifted from blue to red. More importantly, it was demonstrated that r-CDs (red CDs) can produce different independent long-wavelength fluorescence emissions ranging from green to red by dispersing CDs into different solvents. Moreover, the as-prepared r-CDs exhibited a response to the changes in pH values and showed apparent color changes from reddish brown to light purple visible to the naked eye in daylight. With low cytotoxicity and tunable emissions, our CDs show potential in solvent sensing, pH sensing and bio-labeling.